Serum free light chain ratio as a biomarker for high-risk smoldering multiple myeloma - Larsen, JT (2012)
A markedly elevated serum free light chain (FLC) ratio may serve as a biomarker for malignant transformation in high-risk smoldering multiple myeloma (SMM) and identify patients who are at imminent risk of progression. We retrospectively studied the predictive value of the serum (FLC) assay in 586 patients with SMM diagnosed between 1970 to 2010. A serum involved/uninvolved FLC ratio ≥100 was used to define high-risk SMM, which included 15% (n = 90) of the total cohort. Receiver operating characteristics analysis determined the optimal FLC ratio cut-point to predict progression to symptomatic multiple myeloma (MM) within 2 years of diagnosis, which resulted in a specificity of 97% and sensitivity of 16%. Fifty-six percent of patients developed progressive disease during median follow-up of 52 months, but this increased to 98% in the subgroup of patients with FLC ratio ≥100. The median time to progression in the FLC ratio ≥100 group was 15 months versus 55 months in the FLC <100 group (P<0.0001). The risk of progression to MM within the first 2 years in patients with an FLC ratio ≥100 was 72%; the risk of progression to MM or light chain amyloidosis in 2 years was 79%. We conclude that a high FLC ratio ≥100 is a predictor of imminent progression in SMM, and such patients may be considered candidates for early treatment intervention.